Acute Effect of Transcranial Direct Current Stimulation in Pelvic Floor Muscle Function in Young Healthy Women: Initial Findings of a Randomized Controlled Trial - Ledur, Ângela C.; Fontenele, Marta Q. S.; Bueno, Maria E. B.; Smaili, Suhaila M.; Zamboti, Camile L. [UNESP] (Springer Nature, 2024)
Introduction and Hypothesis: Transcranial direct current stimulation (tDCS) can enhance muscle function in healthy individuals. However, it is unknown if tDCS associated with pelvic floor muscle training (PFMT) can improve pelvic floor muscle function (PFMF) in healthy women. The aim of this study was to investigate the acute effect of a single session of tDCS in PFMF compared with sham-tDCS in healthy women. Methods: A double-blind, cross-over, randomized clinical trial was conducted with healthy, nulliparous and sexually active women. PFMF was assessed by bidigital palpation (PERFECT scale) and intravaginal pressure by a manometer (Peritron™). Participants randomly underwent two tDCS sessions (active and sham) 7 days apart. The electrode was positioned equal for both protocols, the anode electrode in the supplementary motor area (M1) and the cathode electrode in the right supraorbital frontal cortex (Fp2). The current was applied for 20 min at 2 mA in active stimulation and for 30 s in sham-tDCS. The tDCS applications were associated with verbal instructions to PFMT in a seated position. After each tDCS session PFMF was reevaluated. Results: Twenty young healthy women (aged 23.4 ± 1.7 years; body mass index 21.7 ± 2.2 kg/m2) were included. No difference was observed in power, endurance, and intravaginal pressure of PFMF (p > 0.05). The number of sustained contractions improved from 3.0 (2.0–3.5) to 4.0 (3.0–5.0) after active-tDCS (p = 0.0004) and was superior to sham-tDCS (p = 0.01). Conclusion: The number of sustained contractions of PFM improved immediately after a single active-tDCS session, with a difference compared with the post-intervention result of sham-tDCS in healthy young women.
Keywords: Muscle strength; Non-invasive brain stimulation; Pelvic floor; Randomized controlled trial; Transcranial direct current stimulation; Women